A Genealogy of the Author: from Auctors to Commercial Writers - Barrientos, Maynor (2006)
The following essay is a brief genealogical review on the origin and evolution of the concept of the author in literary criticism, and of its role in the production and distribution of books and printed material. This essay begins with an analysis of the medieval concept of the auctor, an anonymous agent of Western monarchical authority, and ends up with the use of the concept of the author to define a large group of writers, among which 19th century commercial writers stand out. Moreover, the word authorship, its use and concept, is also analyzed, as well as its role in the economic and social development of Western communities from the discovery of America to the 19th century. Briefly, there is also a parallel analysis of those technological, philosophical, structural and ideological changes that catapulted the evolution of the concept of the author to its more contemporary uses.